MOTIVASI STAF MEMILIH PROFESI PARENTAH SYARA’ DALAM MENGELOLA MASJID AL-MUHIBBIN NEGERI MAMALA KECAMATAN LEIHITU - Mahdi Malawat Alhatam Lestaluhu (DIALEKTIKA, 2018)
Parentah Syara 'is the unit manager of the mosque which is based on local wisdom. This study deals with motivation Parentah Syara 'as manager of Al-Muhibbin Mamala Leihitu District State Central Maluku. In this case there are two motivations associated with the experience of the staff Parentah Syara, 'The first is because the motivation and motivation for a purpose why they served or worked as Parentah Syara'. This study is based on the perspective of social action, social construction, and phenomenology with research methodology in-depth interviews and participant observation in order to obtain the data in the field. By using the interpretive paradigm is subjective this study serve as the basic foundation for understanding Parentah Syara '. The method used is qualitative research methods with the subject of research is the staff who work as Parentah Syara 'Masjid Al-Muhibbin Mamala State. Results of interviews and observations of researchers regarding the motivation of the staff Parentah Syara ', researchers have developed a typology construction of meaning associated with childbirth experience motivation. The staff Parentah Syara 'as the subject is considered to have a cause and motive motive purpose of carrying out tasks in the management of the mosque. Subjects were less satisfied with the performance of those due to different understandings of the nature of Parentah Syara